Logical and Epistemological Approaches to Educational Research: A Philosophical Inquiry - Goswami, Ayushman (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Logic plays an important role in the understanding of the nature of knowledge and the very process of its acquisition. In other words, logic can be considered as a rational basis of ‘science’ in order to become a systematic and intellectual approach towards understanding the world around us. This has also been a fundamental task of ‘philosophy’ too, as ‘Epistemology’ is supposed to do what is expected from logic. This paper is an initial attempt to explore logical and epistemological approaches to educational research. It will welcome suggestions to proceed ahead towards philosophical research in education.